Indications for use of damage control surgery in civilian trauma patients: a content analysis and expert appropriateness rating study - Roberts, D; Bobrovitz, N; Zygun, D; Ball, C; Kirkpatrick, A; Faris, P; Brohi, K; D'Amours, S; Fabian, T; Inaba, K; Leppäniemi, A; Moore, E; et al. (Lippincott, Williams & Wilkins, 2016)
Objectives: To characterize and evaluate indications for use of damage control (DC) surgery in civilian trauma patients. Background: Although DC surgery may improve survival in select, severely injured patients, the procedure is associated with significant morbidity, suggesting that it should be used only when appropriately indicated. Methods: Two investigators used an abbreviated grounded theory method to synthesize indications for DC surgery reported in peer-reviewed articles between 1983 and 2014 into a reduced number of named, content-characteristic codes representing unique indications. An international panel of trauma surgery experts (n = 9) then rated the appropriateness (expected benefit-to-harm ratio) of the coded indications for use in surgical practice. Results: The 1107 indications identified in the literature were synthesized into 123 unique pre- (n = 36) and intraoperative (n = 87) indications. The panel assessed 101 (82.1%) of these indications to be appropriate. The indications most commonly reported and assessed to be appropriate included pre- and intraoperative hypothermia (median temperature <34°C), acidosis (median pH <7.2), and/or coagulopathy. Others included 5 different injury patterns, inability to control bleeding by conventional methods, administration of a large volume of packed red blood cells (median >10 units), inability to close the abdominal wall without tension, development of abdominal compartment syndrome during attempted abdominal wall closure, and need to reassess extent of bowel viability. Conclusions: This study identified a comprehensive list of candidate indications for use of DC surgery. These indications provide a practical foundation to guide surgical practice while studies are conducted to evaluate their impact on patient care and outcomes.